Analysis on C++ Topic Difficulties Ranking: A Case Study on Mechanical Engineering Students in UiTM Pasir Gudang - Hasmy, Harshida; Ibrahim, Nur Syafikah; Kapi @ Kahbi, Azyan Yusra (International Journal of Human and Technology Interaction (IJHaTI), 2020)
The aim of this paper is to analyse student’s performance obtained from the course “Fundamentals of Computer Problem Solving” (CSC128) final examination results. This is a C++ programming course and it is a mandatory subject for all Diploma in Mechanical Engineering and Diploma in Civil Engineering students at Universiti Teknologi MARA Pasir Gudang Campus. Through the analysis, this paper identify which topics in CSC128 is not being well mastered by the students. The data was collected from 163 students score marks and the analysis was conducted by categorizing the final examination questions into five different topics according to CSC128 syllabus. An indicator has been used to classify students’ performance for each topic by comparing the percentage of students who scored 50% above and below of total marks for every topic. The study identified that Topic 4, “Repetition Control Structure” was placed in the first rank as the most difficult topic encountered by the students and Topic 3, “Selection Control Structure” was ranked as the least difficult topic. The findings will be used to improve the subject in order to achieve the course outcomes and can be a guideline for the lecturers to improve their teaching method in order to increase students’ understanding, interest and performance in programming.